Nutritional value of a spray-dried freshwater alga, Spongiococcum excentricum, for Pacific oyster (Crassostrea gigas) spat - Knauer, J; Southgate, Paul C (Aquaculture, 1996)
The nutritional value of a spray-dried freshwater alga (Spongiococcum excentricum) for Pacific oyster (Crassostrea gigas) spat was assessed in two growth experiments. In Experiment 1, spat were fed for 28 days on mixtures of a live diatom, Chaetoceros muelleri, and rehydrated S. excentricum. Growth rates were positively correlated with the amount of live algae in the diet. However, neither the dry weight nor the ash free dry weight (AFDW) of spat fed a 100% C. muelleri (100%C) diet were significantly higher than those of spat fed an 80% C. muelleri: 20% S. excentricum (80%C:20%S) diet. The protein, lipid and carbohydrate content of spat also increased with a higher percentage of live C. muelleri in the diet, but again there were no significant differences between spat fed 100%C and spat fed an 80%C:20%S diet. The nutritional contribution of S. excentricum was furthermore indicated by the significantly higher AFDW of spat fed 80%C:20%S compared to spat fed an 80% ration of C. muelleri alone. S. excentricum could therefore potentially substitute a live algal diet at a 20% replacement level. In Experiment 2, S. excentricum was supplemented with either 5 or 20 mg kaolin l-1. The growth of C. gigas spat did not improve significantly at either level of supplementation with kaolin compared with spat fed S. excentricum alone.